Effect of diffusion of I group metal (Ag) on characteristics of metal/porous silicon sensors - Dzhafarov, T. D.; Aydin, S.; Oren, D. (TRANS TECH PUBLICATIONS LTD, 2008)
Current-voltage characteristics of Schottky-type Ag/Porous Silicon (Ag/PS) structures in normal air, humid ambient and in different hydrogen-containing solutions (distilled water, freshwater, Black sea-water, ethanol ad methanol) have been investigated. Generation of the open-circuit voltage (V-oc), short-circuit current (J(sc)) up to 560 mV and 0.5mA/cm(2), respectively, on placing Ag/PS structures in hydrogen-containing solutions was discovered. This phenomenon is reversible, i.e. placing and removal of Ag/PS structures cell from hydrogen-containing solutions is accompanied by response and recovery of the V., and Jsc parameters. It is shown that the thermal annealing of the Ag/PS structure at 200 degrees C for 10 min is accompanied by somewhat changes and stabilization of V-oc and J(sc) parameters of Ag/PS sensors. The possible mechanisms related with hydrogen-stimulated generation of voltage and diffusion-stimulated stabilization of the sensing parameters of Ag/PS Schottky-type structures is suggested. Data received in this work indicate on perspectivity of using Ag/PS structures as both the gas sensors and hydrogen cells.
Keywords: porous silicon; Ag; diffusion; gas sensor; hydrogen cell; HUMIDITY-VOLTAIC CHARACTERISTICS; PS-SI STRUCTURES; Materials Science; Physics